1981
DOI: 10.3171/jns.1981.55.5.0678
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of 54 traumatic carotid-cavernous fistulas

Abstract: A series of 54 traumatic carotid-cavernous fistulas has been treated with detachable balloon catheters. The balloon was introduced through one of three different approaches: the endarterial route; the venous route through the jugular vein, the inferior petrosal sinus, and the cavernous sinus; or surgical exposure of the cavernous sinus; with occlusion of the fistula by a detachable balloon directly positioned in the cavernous sinus. Full follow-up review demonstrated that the carotid blood flow was preserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0
8

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(149 citation statements)
references
References 19 publications
3
138
0
8
Order By: Relevance
“…A localização da fístula é em sua maioria no segmento horizontal da ACI intra-cavernosa, com 41% dos casos, e em 29% dos casos na junção dos segmentos horizontal e ascendente posterior. A junção da porção horizontal com a ascendente anterior responde a 9% dos casos e apenas 2% ocorre no segmento ascendente anterior 6 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A localização da fístula é em sua maioria no segmento horizontal da ACI intra-cavernosa, com 41% dos casos, e em 29% dos casos na junção dos segmentos horizontal e ascendente posterior. A junção da porção horizontal com a ascendente anterior responde a 9% dos casos e apenas 2% ocorre no segmento ascendente anterior 6 .…”
Section: Discussionunclassified
“…Estas são lesões de alto fluxo e alta pressão e possuem incidência baixa de hemorragias. Fístulas carótido-cavernosas (FCCs) são um tipo específico de fístula arteriovenosa e representam comunicações anormais entre a artéria carótida interna (ACI) e o seio cavernoso, surgindo de modo incomum, porém, não raro [1][2][3][4][5][6][7][8] . Inicialmente podemos dividir todas as FCCs em espontâneas e pós-traumáticas.…”
unclassified
“…Third and sixth nerve palsy after balloon embolization has also been observed. Debrun et al [20] reported a 20% incidence of transient oculomotor nerve palsy, which is usually combined to sixth cranial nerve dysfunction.…”
Section: Review Of Endovascular Management Of Traumatic Carotid-cavermentioning
confidence: 99%
“…La mayoría de las FCC directas pueden cerrarse mediante tratamiento endovascular, generalmente por vía arterial mediante coils o balones 8,17 , aunque también se han obtenido buenos resultados por vía venosa 13 . El tratamiento de las FCC indirectas o durales es más complicado, siendo la vía venosa de elección para la mayoría de los autores 1,7,12,18,21,26 .…”
Section: Introductionunclassified